Long Non-coding RNAs Contribute to the Inhibition of Proliferation and EMT by Pterostilbene in Human Breast Cancer - Yongye Huang; Juan Du; Yan Mi; Tianye Li; Ying Gong; Hongsheng Ouyang; Yue Hou (Frontiers in Oncology, 2018)
Background: There is increasing evidence that long non-coding RNAs (lncRNAs) are involved in the process of carcinogenesis and treatment using chemotherapy. Pterostilbene, a phytochemical agent with natural antioxidant and anti-inflammatory properties, has been shown to modulate oncogenic processes in many cancers. However, there has been limited research on the association between pterostilbene and the expression of lncRNAs.Methods: MCF7 breast cancer cells were treated with various concentrations of pterostilbene and their gene expression profile was analyzed by quantitative real-time PCR, Western blotting and immunofluorescence.Results: Treatment with pterostilbene inhibited cell proliferation and epithelial-to-mesenchymal transition (EMT), and increased cell apoptosis, autophagy and ER stress. The Akt/mTOR pathway was downregulated, but p38 MAPK/Erk signaling was activated in cells following treatment with pterostilbene. Pterostilbene increased the expression of the lncRNAs MEG3, TUG1, H19, and DICER1-AS1 whereas the expression of LINC01121, PTTG3P, and HOTAIR declined. Knockdown of lncRNA H19 resulted in a reduction of the cell invasion, with the cells becoming more sensitive to pterostilbene therapy.Conclusions: These results suggest that efficient optimum disruption of lncRNA expression might possibly improve the anti-tumor effects of phytochemical agents, thus serving as a potential therapy for breast cancer.